Pembadanan Prinsip Kepemerintahan yang Baik (Good Governance) dalam Penerbitan Izin Usaha Pertambangan (IUP) (Studi Kasus di Sulawesi Tenggara) - Oheo K. Haris (Perspektif Hukum, 2015)
This work is aimed at exploring appropriate method in embodying and applying the principle of good governance in managing strategic resources, i.e in issuing mining license. Governing this mining actually has crucial matters in order to underpine a huge value as well as benefit toward the economic growth and sustainable development. This effort is importance to prevent maladministration, corruption, and the deterioration of environmental quality that may block the sustainable development. This maladministration in issuing mining license has created complexity and overlap administrative decisions, either at the vertical or horizontal. At the vertical level the tension, conflicted, and overlapped administrative decision could be seen between central and local government, whereas at horizontal level, conflicted decision could be seen at sectoral department. For that reason, this work offers an appropriate method in integrating and embodying the principle of good governance, such as transparency, carefulness, and proportionality in issuing mining license. The application of this method may create a holistic and integrated policy in managing and optimizing collective strategic resources for the greatest benefit for greatest number of people.